Science, parascience, art: mechanisms of convergence - Shamyakina, Tat’yana I. (Journal of the Belarusian State University. Sociology, 2019)
The problems of science are examined, the main stages are delineated and, in this case, the paradoxes of its development. Attention is focused on the differences and the moments of the convergence of science and art, their influence on each other. The question of myths in science is touched upon. Discussions are given about the possibility of a new paradigm in education, based on the current state of science and art. Rich empirical material is involved.